Matlab in quality assurance sciences - Burstein, Leonid (Woodhead Publishing in mechanical engineering., 2015)
MATLAB® in Quality Assurance Sciences fills a gap in the highly topical field of quality assurance (QA). It is a compact guide for students, engineers, and scientists in this field. It concentrates on MATLAB® fundamentals with examples of application to a wide range of current problems from general, nano and bio-technology, and statistical control, to medicine and industrial management. Examples cover both the school and advanced level; comprising calculations of total quality management, six sigma, time series, process improvement, metrology, quality control, human factors in quality assuran.